The Role of Job Satisfaction in Mediating the Influence of Leadership and Organizational Culture on Lecturer Performance at the Faculty of Dentistry, Mahasaraswati University Denpasar (International Journal of Scientific Research and Management (IJSRM), 2024)
The transformation of online learning during the pandemic raises complex challenges for lecturers. This has an impact on dissatisfaction from both lecturers and students. In addition, the transformation of organizational culture puts additional pressure on lecturer performance, making the leadership role very important in managing workload and providing flexibility. This research aims to investigate the role of job satisfaction as a mediator in connecting the influence of leadership and organizational culture on the performance of lecturers at the Faculty of Dentistry, Mahasaraswati University, Denpasar during the pandemic. The population in this study were 60 permanent lecturers at the Faculty of Dentistry, Mahasaraswati University. The data collection method in this research is through interviews, questionnaires, observation and documentation. This research uses SEM PLS as a data analysis technique. The results of this research show that: (1) Leadership has a positive and significant effect on lecturer performance, (2) Organizational culture has a positive and significant effect on lecturer performance, (3) Leadership has a positive and significant effect on lecturer job satisfaction, (4) Organizational culture has an effect positive and significant on lecturer job satisfaction. (5) Job satisfaction has a positive and significant effect on lecturer performance, (6) Job satisfaction mediates the influence of leadership on lecturer performance, (7) Job satisfaction mediates the influence of organizational culture on lecturer performance.